Health state preferences and decision-making after malignant middle cerebral artery infarctions [Image: see text] [Image: see text] [Image: see text] - Kelly, Adam G. (American Academy of Neurology, 2010)
OBJECTIVES: Despite recent trials demonstrating improved functional outcomes in patients with malignant middle cerebral artery ischemic strokes treated with hemicraniectomy, survivors still experience significant stroke-related disability. The value assigned to health states with significant disability varies widely and may influence decisions regarding hemicraniectomy. METHODS: A medical decision analysis was used to evaluate the results of recent hemicraniectomy trials in terms of quality-adjusted life-years. Survival data and probability of various functional outcome states (modified Rankin score 2–3 or 4–5) at 1 year were abstracted from clinical trial data. Utility scores for modified Rankin states were abstracted from literature sources. Sensitivity analyses were performed to study results over a wide range of utility values. All modeling was performed on TreeAge Pro software. RESULTS: The hemicraniectomy treatment pathway was associated with more quality-adjusted life-years over the first year than the medical management pathway (0.414 vs 0.145). Hemicraniectomy remained the preferred option except when the utility associated with the possible outcome states dropped considerably (0.72 to 0.40 for Rankin 2–3, and 0.41 to 0.04 for Rankin 4–5), or when 1-week surgical mortality increased considerably (5% to 67%). CONCLUSIONS: Over a 1-year time horizon, treating patients with malignant middle cerebral artery strokes with hemicraniectomy is associated with more quality-adjusted life-years than medical management alone, except under conditions where patients value possible resultant health states very poorly or surgical mortality is excessively high. GLOSSARY: MCA: = middle cerebral artery; QALY: = quality-adjusted life-year; QOL: = quality of life.